Effect of intensive water-salt diet nursing intervention on blood pressure and volume load in patients with chronic renal failure - Liyan Wu; Wanli Ma; Hui Zhang; Ting Yang; Mengxi Sun; Zhen Yang; Xiaohan Guo (Renal Failure)
Background This study aimed to investigate the impact of a comprehensive nursing intervention targeting high water and salt intake on blood pressure and volume burden in patients with chronic renal failure.Method From January 2020 to January 2023, 120 patients diagnosed with chronic renal failure were treated at our hospital. Participants were randomly allocated to either a control group (n = 60) receiving standard dietary education or an observation group (n = 60) receiving intensive water-salt diet nursing intervention alongside standard education. Blood pressure, volume load, and related parameters were compared after a 6-month observation period.Result Both groups exhibited reduced systolic and diastolic blood pressure post-intervention (p < 0.05). The observation group demonstrated a significantly lower extracellular water-to-total body water ratio (ECW/TBW) compared to the control group (p < 0.05). The observation group also showed higher 24-hour urine volume (p < 0.05), hemoglobin levels, creatinine clearance rates (p < 0.05), and treatment compliance (p < 0.05), alongside a lower complication rate (3.33% vs. 13.33%; χ2 = 3.927, p < 0.05). A negative correlation was observed between the Therapeutic Intervention Scoring System (TISS) scale and post-intervention blood pressure/volume load (r = −2.924, −2.184; p < 0.05).Conclusion Intensive water-salt diet nursing interventions effectively control blood pressure, reduce volume load, and mitigate complications in chronic renal failure patients. This approach should be widely implemented in clinical practice.